Education and Economic Growth in Developing Countries: Empirical Evidence from GMM Estimators for Dynamic Panel Data - Sebki, Wafa (Economics and Business, 2021)
The paper aims at studying the effect of education measured by enrolment ratios in secondary and higher education on economic growth measured by the rate of GDP growth in a sample of 40 developing countries during the period from 2002 to 2016 using the dynamic panel data estimators. The results of estimating the model of this study using the difference GMM estimator or what is known as the Arellano and Bond estimator showed that the proportions of those enrolled in tertiary education had a significant positive effect on economic growth, while the proportions of those enrolled in secondary education had a significant negative effect.